2022
DOI: 10.25174/2582-2675/2022/123943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drought tolerant recombinant inbred lines (RILs) based on selection indices in bread wheat

Abstract: Water scarcity throughout wheat-growing periods is a major issue in India, therefore breeding methods, as well as the efficient selection approaches for moisture stress conditions are required to retain the level of crop production. In the current study recombinant inbred lines were developed through a donor, WH 730 crossed with recipient MACS 2496. Further segregating generations were advanced through the single seed descent method at Karnal. The F 7 and F 8 generations of 231 recombinant inbred lines along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…Results of the pollen and spikelet fertility percent showed variable fertility reactions for the 75 test crosses Tables (3 & 4). Similar results were reported by Chen and Wehling (2003) and Ahirwar et al (2014) who observed a range of complete fertility to complete sterility observed among several hybrid combinations of wheat. The discovery of complete sterility maintainers and complete fertility restorers within wheat genotypes is important in wheat breeding program because it helps in the use of these genotypes in hybrid development.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results of the pollen and spikelet fertility percent showed variable fertility reactions for the 75 test crosses Tables (3 & 4). Similar results were reported by Chen and Wehling (2003) and Ahirwar et al (2014) who observed a range of complete fertility to complete sterility observed among several hybrid combinations of wheat. The discovery of complete sterility maintainers and complete fertility restorers within wheat genotypes is important in wheat breeding program because it helps in the use of these genotypes in hybrid development.…”
Section: Discussionsupporting
confidence: 90%
“…The discovery of complete sterility maintainers and complete fertility restorers within wheat genotypes is important in wheat breeding program because it helps in the use of these genotypes in hybrid development. Ahirwar et al (2014) observed a higher percentage of maintainers and restorers among 130 F1 hybrid wheat. According to these findings, hybrid combinations based on different CMS lines had variable spikelet fertility and pollen fertility.…”
Section: Discussionmentioning
confidence: 85%
“…MP3288 and MP3382 two stress‐tolerant checks confirmed by Khare et al. (2022) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The parents exhibited variation in numerous terminal heat tolerance related traits: grain yield, germination percentage, days to heading, days to maturity, grain filling duration, grain weight per spike, grain number per spike and thousand kernel weight (Gupta et al, 2013;Pandey et al, 2014). MP3288 and MP3382 two stress-tolerant checks confirmed by Khare et al (2022) were included in this study.…”
Section: Development Of Experimental Materialsmentioning
confidence: 99%
“…Fluctuating climate is expected to affect various biotic as well as abiotic stresses on wheat (Prasad et al, 2021). The constantly rising temperature of the planet has resulting in water depletion thus limiting the agricultural yield of the crops (Khare et al, 2022). Drought has a very negligible influence on the incidence of kernel filling in wheat, but it does reduce the period between fermentation and maturity, resulting in lowering the dry weight at maturity (Wardlaw and Willenbrink 2000).…”
Section: Introductionmentioning
confidence: 99%